Complexation of Cm(III) and Eu(III) with CyMe4-BTPhen and CyMe4-BTBP studied by time resolved laser fluorescence spectroscopy - Bremer, Antje; Whittaker, Daniel M.; Sharrad, Clint A.; Geist, Andreas; Panak, Petra (Dalton transactions, 2014)
The complexation of Cm(III) and Eu(III) with 2,9-bis(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-1,2,4-benzotriazin-3-yl)-1,10-phenanthroline (CyMe4-BTPhen) and 6,6′-bis(5,5,8,8-tetramethyl-5,6,7,8-tetrahydro-1,2,4-benzotriazin-3-yl)-2,2′-bipyridine (CyMe4-BTBP) in methanolic solution was investigated by TRLFS. For both ligands, the 1:2 complex with the particular metal ion is the only species observed in equilibrated samples. The species distribution for various ligand concentrations was determined and stability constants of the 1:2 complexes were derived (log β2 = 13.8 ± 0.2 (Cm(III)-CyMe4-BTPhen), log β2 = 11.6 ± 0.4 (Eu(III)-CyMe4-BTPhen), log β2 = 12.4 ± 0.3 (Cm(III)-CyMe4-BTBP) and log β2 = 11.3 ± 0.3 (Eu(III)-CyMe4-BTBP)). Biphasic experiments in combination with TRLFS studies on the organic phase revealed the formation of ternary complexes with two CyMe4-BTPhen or -BTBP molecules and additional coordination of a nitrate anion as species formed during the extraction process.